Monitoring of bacterial diseases of Agaricus bisporus in Serbia - Milijašević-Marčić, Svetlana; Todorović, Biljana; Stepanović, Miloš; Duduk, Bojan; Stepanović, Jelena; Rekanović, Emil; Potočnik, Ivana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
Monitoring of button mushroom bacterial diseases was conducted to estimate the presence and identity of mycopathogenic bacteria and to determine the predominant bacterial pathogen in Serbia. Samples were collected from mushroom farms during 2006-2010 and also from fresh markets during 2014-2015. The collected samples showed either symptoms of brown blotch or different degrees of brown discoloration on caps and stalks of Agaricus bisporus resembling bacterial infection. The presence of bacterial droplets on gills was not recorded. The isolated bacteria were Gram-negative and fluorescent on King’s medium B. In pathogenicity tests, most bacterial isolates induced superficial or sunken brown lesions with differences in the level of discoloration on A. bisporus tissue blocks after artificial inoculation. Based on LOPAT characteristics, the isolates were divided into two groups, showing characteristics of either the LOPAT group Va or group III. Based on these features and other differential biochemical characteristics, the presumptive Pseudomonas tolaasii isolates were confirmed by specific PCR. The other group of isolates was subjected to sequencing of the 16S rDNA. Based on these sequences most isolates were identified as Pseudomonas agarici, while two strains belonged to Pseudomonas fluorescens. The survey resulted in detection and identification of P. tolaasii in 11 locations and P. agarici in 7 locations in Serbian mushroom farms. Most samples from fresh markets were infected with P. tolaasii, suggesting that this pathogen has been the predominant cause of bacterial diseases in Serbian mushroom-growing facilities over the past 10 years.